Identifikasi Varietas Jagung Menggunakan Metode Convolutional Neural Network - Idin, Abdurrahim Ramadhan; Kustiyo, Aziz; Agmalaro, Muhammad Asyhar; Haryanto, Toto (JELIKU (Jurnal Elektronik Ilmu Komputer Udayana), 2025)
Keywords : Image Processing, Drought Stress, Convolutional Neural Network, Seed Identification, Corn